Two years of psychogeriatric consultations in a nursing home: reasons for referral compared to psychiatrists' assessment - Costantini Chiara; Beraldo Scilla; Croci Giovanni; Menchetti Marco; Callegari Camilla MT; Baranzini Federico (BMC, 2006)
Abstract Background In spite of the high prevalence of psychiatric disorders among elderly residents in nursing homes, only a small number of patients in need of specialist care are referred to a psychiatric consultant. The aim of this research was to evaluate the consultation activity and the appropriateness of referral to psychiatric assessment. Methods Data were collected and analysed on consultation carried out over a two-year period in a RSA (Residenza Socio-Assistenziale) in Northern-Italy. Data were catalogued with reference to: patients, consultation, diagnosis and recommended medications. Statistical correlation analysis by means of Spearman test and signification test was carried out. Results Residents referred to psychiatric consultation at least once were 112 (14.5% of all residents). Reason for referral were: depression (17.2%), delusions and hallucinations (14%), agitation (34.8%), aggressive behaviour (23.5%) and disturbances of sleep (6.8%). Most frequent diagnoses were organic, including symptomatic, mental disorders (33.9%), mood disorders (22.3%) and schizophrenia, schizotypal and delusional syndromes (18.8%). No psychiatric diagnosis was found only in 1.8% of cases, thus confirming high sensibility of referring physicians. A statistically significant correlation was found when comparing referrals for depression or delusions and allucinations or sleep disturbances and diagnostic confirmation of such symptoms by specialistic assessment (respectively 49.8%, 52.7% and 19.6%). Correlation between psychotic symptoms and the consequent prescription of antipsychotic drugs had a significant if somewhat modest value (24%) while correlation between depression symptoms and prescription of antidepressant drugs was more noticeable (66.5%). Conclusion Main reason for referral to psychiatric consultation resulted to be the presence of agitation, a non-specific symptom often difficult to attribute. Data concerning depression confirm tendency to underestimating this diagnosis in the elderly. Furthermore, symptomatic reasons for referral did not always correspond to subsequent diagnostic definitions by psychiatric consultants, therefore demonstrating modest predictive power.